Application of Fermented Feed Technology and Semi-Intensive Pig Farming System in the Women's Farmer Group "Suka Nadi" Pejarakan Village, Gerokgak District, Buleleng Regency - Yan Tonga; I Gede Sutapa; I Ketut Agung Sudewa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Bali pig is one of the meat-producing livestock commodities that has great potential to be developed because it has beneficial properties and abilities, but its presence on the island of Bali has begun to decline and is only found in certain areas such as in Buleleng, Karangasem, and Klungkung Regencies. Bali's pig population in Bali Province from 2017-2019 decreased by 27.51%. Likewise, it also occurs in Buleleng Regency by 26.09% and in Pejarakan Village, Gerokgak District, Buleleng Regency by approximately 50%. Some of the factors that influence this decline include feed management and the farming system. Likewise, related to the provision of animal feed ingredients derived from food crops such as corn, bananas, and peanuts, the partners have not really understood in an effort to increase the productivity of these food crops as animal feed. Based the enormous potential and opportunity for Balinese pigs and felt very profitable by the Suka Nadi Peasant Women's Group (KWT) in Pejarakan Village which is located 145 km from the provincial capital with a total of 28 members now still doing Balinese pig farming business on a small scale/household even though it experiences a mortality rate of 25% because in its maintenance it is still with an extensive farming system and makeshift feed. The death of the livestock is caused by being crushed by the mother and getting sick because the livestock lacks the nutrients and feed provided. The problem is that partners do not really understand efforts to increase the productivity of Bali pig livestock, especially regarding the management of the provision and feeding of their livestock. The solution provided is to provide an understanding of knowledge and skills about efforts to increase the productivity of local pig livestock, especially regarding the management of the provision and feeding with fermented feed technology and efforts to increase the productivity of food crops as animal feed ingredients. The method were surveys, interviews, discussions, counseling/training in theory and practice as well as monitoring and evaluation. The output produced is that partners have understood about efforts to increase the productivity of Bali pigs and food crops (corn) as animal feed ingredients and are able to make fermented animal feed so that the provision of feed is more quality, effective and efficient and the partners have a place to make small-scale fermented feed/households.